Microservices and containers - Kocher, Parminder Singh (Addison-Wesley, 2018)
The Complete Guide to Succeeding with Microservices and Docker in Large Software Projects Together, microservices and Docker containers can bring unprecedented agility and scalability to application development and deployment-especially in large, complex projects where speed is crucial but small errors can be disastrous. In Microservices and Containers, Parminder Singh Kocher demonstrates why and how these technologies can help you build, deploy, manage, and scale industrial-strength applications. You'll learn how to leverage microservices and Docker to drive exponential improvements in DevOps effectiveness, on-demand scalability, application performance, time-to-market, code reuse, and application reliability. Kocher also offers detailed guidance and a complete roadmap for transitioning from monolithic architectures, and an in-depth case study walking through the migration of an enterprise-class SOA system. Understand how microservices enable you to organize applications into standalone components that are easier to manage, update, and scale Decide whether microservices and containers are worth your investment, and manage the organizational learning curve associated with them Apply best practices for interprocess communication among microservices Migrate monolithic systems in an orderly fashion Understand Docker containers, installation, and interfaces Network, orchestrate, and manage Docker containers effectively Use Docker to maximize scalability in microservices-based applications This guide will be valuable to software/systems professionals moving from older approaches, architects and developers already working with microservices and containers, and executives and managers seeking to maximize the business value of these technologies.